(untitled) (Journal of Pharmaceutical Negative Results, 2023)
As the informal sector grows and lacks access to formal finance, unlocking its financial potential is crucial. Thus, this study examines innovative solutions for this essential portion of the economy and the interaction between informal and formal markets during economic crises in Nigeria. This study addresses these research questions: How does Nigeria's formal and informal financial markets interact? How does Nigeria's informal financial market affect growth? How does the informal banking sector react to a Nigerian economic shock? This study utilises the open economy Dynamic Stochastic General Equilibrium (DSGE) model. DSGE model parameters were calibrated and computed using Bayesian methods as well as the Dynare 4.6.4 in Matlab R2021a. The impulse response function reveals that monetary shock increased GDP but decreased government expenditure. Examining Nigeria's fiscal, monetary, and production shocks, the study finds that monetary policy shocks increased output and decreased government expenditure, while fiscal policy shocks decreased output and interest rates. The shock indicates that reduction in government spending diminishes aggregate demand as well as the real GDP. Given the informal finance's response to monetary policy shocks, the central bank should, therefore, be more hawkish, especially in times of high inflation, to achieve macroeconomic goals. Thus, the study suggests that future research should examine how the Nigerian economy reacts to shocks like oil shocks.